The treatment of depression — searching for new ideas - Stachowicz, Katarzyna; Sowa-Kućma, Magdalena (Frontiers in Pharmacology, 2022)
Depression is a serious mental health problem that affects people regardless of social status or education, and is associated with changes in mood and behavior, and can result in a suicide attempt. Therapy of depressive disorders is based mainly on drugs discovered in the 1960s and early 1970s. Selective serotonin reuptake inhibitors (SSRIs) and serotonin-norepinephrine reuptake inhibitors (SNRIs) are frontline pharmacological strategies for the medical treatment of depression. In addition, approved by FDA in 2019 esketamine [as nasal spray; N-methyl-D-aspartate (NMDA) receptors antagonist with additional effects on α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors, hyperpolarization-activated cyclic nucleotide-gated (HCN) channels, L-type voltage-dependent calcium channel (L-VDCC), opioid receptors, and monoaminergic receptors] is an essential compound in suicide and drug-resistant depression. However, the treatment of depression is burdened with severe side effects, and in many cases, it is ineffective. An equally important issue is the choice of antidepressant therapy in people with comorbid somatic diseases, for example due to possible interactions with other drugs that the patient is taking. Therefore, there is a great need for new antidepressants with different mechanisms of action and the need to refine the search for new substances. The purpose of this review was to discuss new research directions and new trends that dominate laboratories worldwide. We have reviewed the literature to present new points of the pharmacological target of substances with antidepressant activity. In addition, we propose a new perspective on depressive therapies.